2012
DOI: 10.1016/j.ajhg.2011.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of a Spliceosomal GTPase Encoded by EFTUD2 Causes Mandibulofacial Dysostosis with Microcephaly

Abstract: Mandibulofacial dysostosis with microcephaly (MFDM) is a rare sporadic syndrome comprising craniofacial malformations, microcephaly, developmental delay, and a recognizable dysmorphic appearance. Major sequelae, including choanal atresia, sensorineural hearing loss, and cleft palate, each occur in a significant proportion of affected individuals. We present detailed clinical findings in 12 unrelated individuals with MFDM; these 12 individuals compose the largest reported cohort to date. To define the etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
197
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(213 citation statements)
references
References 25 publications
(33 reference statements)
7
197
1
7
Order By: Relevance
“…The nonsense mutation was previously reported in the same patient by Lines et al 11 (patient 105; Supplementary Table S1 online). A de novo origin of the mutation was confirmed for two patients.…”
Section: Molecular Studiessupporting
confidence: 65%
See 1 more Smart Citation
“…The nonsense mutation was previously reported in the same patient by Lines et al 11 (patient 105; Supplementary Table S1 online). A de novo origin of the mutation was confirmed for two patients.…”
Section: Molecular Studiessupporting
confidence: 65%
“…POLR1D and POLR1C encode subunits of RNA polymerase I and III, respectively, which are involved in the synthesis of ribosomal RNA precursors and small RNAs. 4 Moreover, mutations in EFTUD2 have been identified in patients with MFD and microcephaly or type Guion-Almeida (OMIM 610536), 11 which is characterized by progressive and severe microcephaly, ID, and additional malformations such as choanal and aural atresia, cleft palate, congenital heart defects, and esophageal atresia. 12 However, Gordon et al 12 and Luquetti et al 13 reported EFTUD2 mutations in patients without microcephaly, suggesting that EFTUD2 could be responsible for MFD and microcephaly (MFDM) as well as other forms of MFD.…”
Section: Original Research Article Introductionmentioning
confidence: 99%
“…This suggestion is supported by the tissue-specific defects seen in several genetic syndromes that are characterized by tri-snRNP insufficiency but are compatible with life. adRP, spinal muscular atrophy (SMA), and mandibulofacial dysostosis with microcephaly syndrome (MFDM) are heritable genetic syndromes that stem from heterozygous mutations or deletions in the SMN gene (SMA) or discrete tri-snRNP factors (adRP and MFDM) and consequently lead to haploinsufficiency and impaired tri-snRNP function (Boulisfane et al 2011;Tanackovic et al 2011;Lines et al 2012). Although these mutated splicing factors are ubiquitously expressed, defects are seen in specific cell types or tissues consistent with our data that some cells are more sensitive to perturbations in the tri-snRNP complex.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, mutations in Eftud2 cause craniofacial conditions including mandibulofacial dysostosis and esophageal atresia (Gordon et al 2012;Lines et al 2012;Luquetti et al 2013;Voigt et al 2013).…”
Section: The Role Of Atp6v1c1 In Innate Immunity Regulationmentioning
confidence: 99%